COASTAL COMMUNITY EMPOWERMENT FOR COOPERATIVE ALLIANZ DEVELOPMENT - Johni Harius Putranto; Bambang Sri Wibowo; Teguh Purnomo (Media Mahardhika, 2020)
Natural wealth is an invaluable resource so it must be preserved. Indonesia as an agrarian, archipelago and maritime country located on the equator is one of the countries in the world that has abundant natural resources compared to other countries. To manage these crops, the community and the government support each other in the process of conservation through a positive management process. Institutions related to the process are expected to be able to join hands with the community, so that the community, government and the state can enjoy the results in the long run. One way to help the community, especially in areas far from the center of government, or the community wherever located. Cooperative allianz is one of the solutions that is considered in accordance with the conditions and culture of the community. Because Cooperatives allianz are a form of business that has long existed and been run by Indonesian people since ancient times. As a supporting effort for the development of cooperatives, the government should provide support in the form of training for human resources manager of cooperatives and communities around cooperatives, so that the initial purpose of forming cooperatives can be achieved well and satisfactorily.